2003
DOI: 10.1001/archopht.121.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Presumed Teratoma-Associated Paraneoplastic Retinopathy

Abstract: We thank John T. Harriott, MD, Winston-Salem, NC, for his referral of the patient, his thoughtful input, and his assistance with the care of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…PEPVM is a rare retinal disorder that clinically resembles multifocal Best disease with multifocal yellow-orange deposits in the posterior pole and serous retinal detachments on OCT. [1][2][3]6,7 PEPVM has traditionally been viewed as a paraneoplastic syndrome with numerous reports, describing the condition in association with melanoma. 2,3,5,7,[8][9][10][11]17,[22][23][24][25] It has also been described in association with carcinoma. 3,6 However, the clinically indistinguishable entity, AEPVM, has been reported in association with trauma and various infectious agents, including hepatitis C, Coxsackie B virus, syphilis, and Lyme disease.…”
Section: Discussionmentioning
confidence: 99%
“…PEPVM is a rare retinal disorder that clinically resembles multifocal Best disease with multifocal yellow-orange deposits in the posterior pole and serous retinal detachments on OCT. [1][2][3]6,7 PEPVM has traditionally been viewed as a paraneoplastic syndrome with numerous reports, describing the condition in association with melanoma. 2,3,5,7,[8][9][10][11]17,[22][23][24][25] It has also been described in association with carcinoma. 3,6 However, the clinically indistinguishable entity, AEPVM, has been reported in association with trauma and various infectious agents, including hepatitis C, Coxsackie B virus, syphilis, and Lyme disease.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune retinopathy (AIR) was first recognized as a paraneoplastic disorder as early as 1976 in patients with carcinoma, 1 and subsequent studies in the literature showed that AIR could occur with benign 2 and malignant 3 tumors. Melanoma-associated retinopathy (MAR) was initially reported by Gass 4 in an atypical case with vitelliruptivelike yellow retinal lesions, but most MAR cases have diffuse retinal atrophy without pigment deposits.…”
mentioning
confidence: 99%
“…There have been reports of retinopathies associated with carcinomas, 1 melanomas, 8 tetratomas, 2 and even lymphomas. 9 Most cases of AIR occur in patients without a history of tumors, but occasionally a history of head trauma or preceding intraocular inflammatory disease may be found.…”
mentioning
confidence: 99%
“…Cancer-associated retinopathy (CAR) is a paraneoplastic neurological syndrome (PNS) resulting in progressive loss of vision and clinical signs of retinal degeneration. It is associated with various types of cancer, including small-cell lung cancer (SCLC), non-SCLC, breast cancer, invasive thymoma, uterine cervical cancer, endometrial cancer, lymphoma, and others [ 15 , 16 , 25 , 27 ]. The primary manifestation of CAR is rapid, progressive visual loss due to both rod and cone dysfunction.…”
Section: Introductionmentioning
confidence: 99%